The Effect of Attitude, Subjective Norms, and Achievement Needs on Entrepreneurship Intention (Study on Management S1 Students for the 2018 Beginning) - Zuhrotul Maghfiroh; Andhatu Achsa; Khairul Ikhwan (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
In the 2018 Tidar University Management S1 Study Program, there are only 22 students who are entrepreneurs, while 82 students do not yet have businesses. Students who want to start entrepreneurship need strong intentions so they need to be researched. The influence of attitude variables, subjective norms and achievement needs on entrepreneurial intentions in 2018 undergraduate students management. This study is a quantitative study, the analytical technique used in this study uses IBM SPSS version 25.0. In this study using the saturated sample method with 104 students from the 2018 class as respondents. Collection data techniques in this study using a questionnaire. Outcome of the study partially show that attitude variable affects the entrepreneurial intention, subjective norms affect the entrepreneurial intention, and achievement needs affect the entrepreneurial intention, while simultaneously the independent variable can affects the dependent variable. Suggestions are give for further research by deepen the variables study, for universities by involving and support entrepreneurship activities, for students by attending seminars, workshops, and entrepreneurship training.